Evaluation of CORDEX Regional Climate Models in Simulating Extreme Dry Spells in Southwest China - Feng, Tao; Tipton, Zachary; Xia, Lan; Chang, Youli (Frontiers in Earth Science, 2019)
In recent decades, Southwest China (SWC) has experienced a series of severe and extensive droughts resulting in tremendous socioeconomic losses. The annual maximum dry spell length (AMDSL), which refers to the number of consecutive days without rainfall, or days with rainfall below a threshold, plays an important role in triggering drought. The main objective of this study is to provide a comparison of the capabilities of current regional climate models (RCMs) in simulating extreme dry spell characteristics in mountainous SWC. Five available RCM simulations utilized in the Coordinated Regional Climate Downscaling Experiment (CORDEX)-East Asia project over 1981 to 2005 were employed in this study; the RCMs being NIMR-HadGEM3, SNU-MM5, SNU-WRF, KNU-RegCM4 and YSU-RSM. Firstly, it was found that all RCMs reasonably simulate the main seasonality features of rainfall and dry days in SWC. Furthermore, besides YSU-RSM, the other four RCMs can accurately capture the spatial pattern of dry-day occurrence based on Taylor diagram diagnosis. Secondly, we assessed the performance of five RCMs to detect and reproduce the climatology and variability of the AMDSL. In general, RCMs simulate the spatial pattern of long-term mean and interannual variability of the AMDSL in SWC well. Based on Taylor diagram evaluation, NIMR-HadGEM3 was the best among 5 RCMs in simulating the AMDSL characteristics. Thirdly, the generalized extreme value (GEV) distribution is considered the most suitable model fitting the AMDSL in both observation and RCM experimental data in comparison to other three-parameter probabilistic models. Higher value centers of the scale parameter and the location parameter indicate a wider and amplified distribution of the AMDSL over the low-latitude highlands (LLH) region against other areas in Southwest China, which is consistent with spatial patterns of climatological AMDSL. In addition, sensitivity analysis of different thresholds for dry days show that the 1 mm threshold is suitable for this study and different threshold choices have little effect on simulation ability.